Verflochtene Vergangenheiten:: Geschichtscomics in Europa, Asien und Amerika. Perspektiven auf ein Forschungsfeld - Kesper-Biermann, Sylvia; Severin-Barboutie, Bettina (Comparativ, 2014)
Providing the introduction to this special issue, the article explores, in three steps, history comic books as a field of research that has so far been neglected by transnational history. First, it highlights the significance of cross-border impacts on comics and enquires into transnational exchange and demarcation processes. Thus, the usual, often unconsciously nationalised focus on the three main, i.e. US, Japanese and French-Belgian, comic cultures is challenged and it is asked for a closer look at so far disregarded areas. Second, history comic books are characterised by entanglements between facts and fiction, the overlap of different time layers and transnational crossings. It is argued that Germany during the second half of the 20th century constitutes a particularly suitable object for studying these issues, since it can be characterised as “a site for intercultural exchange” with regard to picture books representing the past. The third part eventually points out prospects for future research in history comic books as entangled pasts.